A X/Ku dual‐band reflectarray design with cosecant squared shaped beam. Issue 9 (September 2014) - Pan, Yu; Zhang, Yan (Rockee); Yu, Xining
ABSTRACT A X/Ku dual‐band center‐fed microstrip reflectarray antenna with cosecant squared shaped beams has been developed. The circular reflectarray has a radius of 0.3 m and a flat aperture that emulates a cylindrical reflector antenna. The reflectarray is designed for two frequency bands: 10 GHz (X band) and 15 GHz (Ku band). Cross‐dipole elements and double‐ring elements are uniquely applied on a dual‐layer structure to achieve the desirable dual‐band operations. As the two operation frequency bands are close to each other, the coupling effects of the dual‐band reflectarray elements are investigated, and the unit cell design is optimized in simulations to suppress the interband interference. A phase‐only synthesis technique for cosecant squared patterns is also discussed and realized. For demonstration purpose, prototype antenna is fabricated and measured and the measured results are compared with the simulation results. © 2014 Wiley Periodicals, Inc. Microwave Opt Technol Lett 56:2028–2034, 2014